2023
DOI: 10.1002/ejhf.3003
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in long‐term outcomes following acute heart failure hospitalization: Findings from the Get With The Guidelines‐Heart Failure registry

Neil Keshvani,
Sonia Shah,
Iyanuoluwa Ayodele
et al.

Abstract: Background and AimsSex differences in long‐term outcomes following hospitalization for heart failure (HF) across ejection fraction (EF) subtypes are not well described. In this study, we evaluated the risk of mortality and re‐hospitalization among males and females across the spectrum of EF over 5 years of follow‐up following an index HF hospitalization event.MethodsPatients hospitalized with HF between 1/1/2006–12/31/2014 from the AHA's GWTG‐HF registry with available 5‐year follow‐up using Medicare Part A cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Advances in GDMT have resulted in the potential for a >70% relative risk reduction in cardiovascular death and HF hospitalization compared with placebo, 24 yet most of these gains have not been realized with minimal improvements in mortality seen over the past 2 decades in registry populations. [25][26][27] The crux of the disconnect lies in the suboptimal initiation and titration of GDMT in HFrEF populations. Analysis of the CHAMP-HF (Change the Management of Patients With Heart Failure) registry showed that just 1% of patients were on optimal GDMT therapy and dose.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in GDMT have resulted in the potential for a >70% relative risk reduction in cardiovascular death and HF hospitalization compared with placebo, 24 yet most of these gains have not been realized with minimal improvements in mortality seen over the past 2 decades in registry populations. [25][26][27] The crux of the disconnect lies in the suboptimal initiation and titration of GDMT in HFrEF populations. Analysis of the CHAMP-HF (Change the Management of Patients With Heart Failure) registry showed that just 1% of patients were on optimal GDMT therapy and dose.…”
Section: Discussionmentioning
confidence: 99%
“…2,[9][10][11][12][13] Among 155 670 patients hospitalized with HF enrolled in the American Heart Association's Get With The Guidelines-Heart Failure registry, females (vs. males) had a greater loss in survival time than the median age-and sex-matched US population and had a greater risk of rehospitalization over 5 years following HF hospitalization. 14 Effective decongestion is the main goal of short treatment of patients with acute HF. 2,10,[15][16][17][18] [20][21][22][23][24] These data and their implications for outcomes were reviewed by Packer and Butler.…”
Section: Acute Heart Failurementioning
confidence: 99%
“…Acute HF remains a turning point in the clinical history of the patients with HF, associated with a marked worsening of quality of life (QoL) and poorer outcomes 2,9–13 . Among 155 670 patients hospitalized with HF enrolled in the American Heart Association's Get With The Guidelines‐Heart Failure registry, females (vs. males) had a greater loss in survival time than the median age‐ and sex‐matched US population and had a greater risk of rehospitalization over 5 years following HF hospitalization 14 …”
Section: Acute Heart Failurementioning
confidence: 99%
“…[4][5][6] Female (compared with male) patients are less likely to have HFrEF than HF with preserved ejection fraction and are more likely to be older at the time of diagnosis. [7][8][9] Female (compared with male) patients are less likely to receive evidence-based device therapy or to undergo coronary revascularization and are more likely to receive treatments that could worsen HF. 10 Furthermore, female (compared with male) patients with HF have a higher burden of symptoms, worse health-related quality of life, higher long-term risk of readmission, and greater loss of survival time after HF hospitalization.…”
mentioning
confidence: 99%
“…10 Furthermore, female (compared with male) patients with HF have a higher burden of symptoms, worse health-related quality of life, higher long-term risk of readmission, and greater loss of survival time after HF hospitalization. 7,9,11,12 Sex differences in cardiovascular pharmacotherapies among patients with coronary artery disease, 13,14 hyperlipidemia, 15 and atrial fibrillation 16,17 are well described. In a pragmatic multicenter trial of patients hospitalized for HF in Canada, female (compared with male) patients receiving usual care had a lower uptake of reninangiotensin system inhibitors and MRAs and a greater uptake of beta-blockers at 30 days after discharge.…”
mentioning
confidence: 99%